A comparison of positive and negative symptoms in Anglo, Latino, and African-American patients with schizophrenia - Weisman de Mamani, Amy Gina; Caldas, Tiffany (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
There are two main classes of schizophrenia symptoms: positive (e.g., hallucinations and delusions) and negative (e.g., flat affect and poverty of speech). Research by Crow (1980, 1985) proposes that negative symptoms indicate irreversible structural brain abnormality and, therefore, unlike positive symptoms, may be less responsive to environmental factors. If Crow’s theory is correct, this might lead us to hypothesize that environmental factors associated with culture and ethnicity may have more of an impact on the expression of positive, rather than negative, symptoms. We aimed to test this hypothesis in the current study. Our sample consisted of 47 patients (16 Anglo, 17 Latino, and 14 African-American) diagnosed with schizophrenia. In line with Crow’s hypotheses, Analyses of Variance (ANOVAs) revealed ethnic differences in positive but not negative symptoms. These results suggest that efforts to target environmental and sociocultural factors may be more effective in reducing positive than negative symptoms.